Factors associated with outpatient satisfaction in tertiary hospitals in China: a systematic review - Li, Yuping; Gong, Weijuan; Kong, Xiang; Müller, Olaf; Lu, Guangyu (International journal of environmental research and public health, 2020)
Outpatient care is made up of medical procedures, tests, and services that can be provided to the patient in a setting that doesn’t involve an overnight hospital stay. In China, tertiary hospitals are medical services centers of health care systems, and some tertiary hospitals had more than 20,000 outpatient visits per day. However, a systematic review of existed evidence on factors influencing the outpatient satisfaction in tertiary hospitals in China could inform the efforts and does not yet exist. Therefore, in order to better understand the outpatient satisfaction provided by tertiary hospitals in China, we carried out a systematic review following PRISMA guidelines. Studies reporting on the level of and factors associated with outpatient satisfaction in Chinese tertiary hospitals were systematically searched in both Chinese and English electronic databases. A total of 36 articles reported 35 studies that met the inclusion criteria. Out of these eight were household surveys covering 12,119 residents, and another 27 directly interviewed 45,930 outpatients during their hospital visits from 185 hospitals. The included studies generally used self-designed questionnaire and indicated there is a lack of standardized questionnaire for investigating outpatient satisfaction in China. The outpatients showed the highest satisfaction with the doctors and nurses and the lowest satisfaction with the hospital hygiene and outpatient procedures, especially with the long waiting time. The socio-demographic characteristics (e.g., age, marital status, income and education levels), professional skills and service attitudes of medical staff were reported to be associated with outpatient satisfaction. The results indicated that in China, the outpatient satisfaction can be largely improved. Firstly, the attitude of medical service providers, especially the pre-diagnosis nurses, registration officers, and pharmaceutical counters should be improved. Furthermore, to shorten the waiting time, policies should be developed to guide patients with common diseases and slight discomforts to community health systems to alleviate the overload in tertiary hospitals. Considering the strained relations between the doctors and patients in the clinical practice, improving patient satisfaction in China deserves more attention and research.